Elections, fiscal policy and fiscal illusion - Mourão, Paulo (2010)
This paper tests the joint hypotheses that policymakers engage in fiscal policy opportunism and that voters respond by rewarding that opportunism with higher vote margins. Furthermore, it investigates the impact of fiscal illusion on the previous two dimensions. Empirical results, obtained with a sample of 68 countries from 1960 to 2006, reveal that opportunistic measures of expenditures and revenues generate larger winning margins for the incumbent and that the opportunistic manipulation of fiscal policy instruments is larger when the current government is less likely to be reelected. Furthermore, fiscal illusion contributes to the entrenchment of incumbent policymakers in office and promotes opportunistic behaviour.